2015
DOI: 10.1002/humu.22743
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Function Variants in Human PNPLA8 Encoding Calcium-Independent Phospholipase A2 γ Recapitulate the Mitochondriopathy of the Homologous Null Mouse

Abstract: Mitochondriopathies are a group of clinically heterogeneous genetic diseases caused by defects in mitochondrial metabolism, bioenergetic efficiency, and/or signaling functions. The large majority of proteins involved in mitochondrial function are encoded by nuclear genes, with many yet to be associated with human disease. We performed exome sequencing on a young girl with a suspected mitochondrial myopathy that manifested as progressive muscle weakness, hypotonia, seizures, poor weight gain, and lactic acidosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 38 publications
3
29
0
Order By: Relevance
“…DNA was prepared utilizing the KAPA Biosystems library preparation kit (KAPA Biosystems, Woburn, MA) followed by Illumina TruSeqExome enrichment (Illumina, San Diego, CA). Alignment and variant calling was performed as previously published [Soden et al, ; Saunders et al, ,]. Using custom‐developed software, RUNES, and VIKING, variants were filtered to 1% minor allele frequency, then prioritized by the American College of Medical Genetics (ACMG) categorization, OMIM (http://www.omim.org) identity and phenotypic assessment.…”
Section: Materials Methods and Resultsmentioning
confidence: 99%
“…DNA was prepared utilizing the KAPA Biosystems library preparation kit (KAPA Biosystems, Woburn, MA) followed by Illumina TruSeqExome enrichment (Illumina, San Diego, CA). Alignment and variant calling was performed as previously published [Soden et al, ; Saunders et al, ,]. Using custom‐developed software, RUNES, and VIKING, variants were filtered to 1% minor allele frequency, then prioritized by the American College of Medical Genetics (ACMG) categorization, OMIM (http://www.omim.org) identity and phenotypic assessment.…”
Section: Materials Methods and Resultsmentioning
confidence: 99%
“…iPLA2γ (PNPLA8) is known to be involved in cardiolipin biosynthesis and mitochondrial respiration[ 27 , 28 ]. Recently, mutations in human PNPLA8 identified in a young girl with a suspected mitochondrial myopathy[ 29 ]. She presented with progressive muscle weakness, hypotonia, seizures, poor weight gain, and lactic acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Data provided by studies of the laboratory mouse have been shown to be valuable in driving discovery of human disease mutations. For example, a recent study describes the discovery of a variant of human PNPLA8 that causes mitochondrial myopathy (OMIM 251950, Saunders et al 2015 ). A mouse mutation in this gene with a similar phenotype had been previously described in Mancuso et al 2009 .…”
Section: Introductionmentioning
confidence: 99%